Partners of young breast cancer survivors: a cross-sectional evaluation of psychosocial concerns, coping, and mental health. Issue 6 (29th September 2020) - Borstelmann, Nancy A.; Rosenberg, Shoshana; Gelber, Shari; Zheng, Yue; Meyer, Meghan; Ruddy, Kathryn J.; Schapira, Lidia; Come, Steven; Borges, Virginia; Cadet, Tamara; Maramaldi, Peter; Partridge, Ann H.
Abstract: Purpose: Evaluation of psychosocial concerns, coping style, and mental health in partners of young (diagnosed at ≤40 years) survivors of early-stage breast cancer (BC). Design: Cross-sectional; partners participated in a one-time survey. Sample: 289 participants; most were male, white, working full-time, college educated, with median age of 43 years, parenting children <18 years old. Methods: Logistic regression was used to explore associations with anxiety and depression (≥8 on Hospital Anxiety and Depression sub-scales). Findings: Overall, 41% reported symptoms of anxiety, 18% reported symptoms of depression, and 44% identified maladaptive coping. Multivariable regression analyses revealed: lower social support and poorer quality of life significantly associated with depression ( p < .05); maladaptive coping, fulltime employment, poorer caregiver QOL, and less education significantly associated with anxiety. Conclusions: Partners of young BC survivors who use more maladaptive coping strategies, report less social support, work fulltime, and/or who have lower education levels experience negative mental health outcomes. Implications for psychosocial oncology: Enhancing constructive coping and ensuring all partners have access to supportive resources may improve partners' emotional adjustment.